2016
DOI: 10.1016/j.chiabu.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental presence and child sexual violence: Evidence from thirteen countries in sub-Saharan Africa

Abstract: There are compelling reasons to believe that orphans – many millions due to the AIDS epidemic – are more likely to be sexually victimized during childhood. Few studies have empirically investigated sexual violence disparities, and those that do suffer from methodological limitations and limited geographic scope. We used nationally-representative data on female adolescents (15-17 years) from 13 countries in sub-Saharan Africa. We built multilevel logistic models to test for an association between the dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 62 publications
(65 reference statements)
3
35
0
1
Order By: Relevance
“…In Canada maternal single marital status was also reported to be associated with allegations of child maltreatment [44]. Further evidence from Sub-Saharan Africa suggests independent associations between paternal orphaning and parental absence and children experiencing sexual violence, with girls being at higher risk of sexual abuse [45]. In South Africa, a study conducted in the Western Cape found that family satisfaction ranked lower among households with absent fathers, partly due to limited economic resources [46].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada maternal single marital status was also reported to be associated with allegations of child maltreatment [44]. Further evidence from Sub-Saharan Africa suggests independent associations between paternal orphaning and parental absence and children experiencing sexual violence, with girls being at higher risk of sexual abuse [45]. In South Africa, a study conducted in the Western Cape found that family satisfaction ranked lower among households with absent fathers, partly due to limited economic resources [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, differences in family organization seem to be related to different types of CAs in terms of vulnerability and profile of parental mental disorders 44. For example, the absence of a parent for any reason places girls at a higher risk of sexual abuse 45…”
Section: Discussionmentioning
confidence: 99%
“…22 Men were not asked these questions, and only a subset of DHS surveys included this scale for women. There was variation between countries in how sexual violence was measured (more information on this measure is available in 23 ).…”
Section: Methodsmentioning
confidence: 99%